Ambient Intelligence - Software and Applications -, 9th International Symposium on Ambient Intelligence - Novais, Paulo; Jung, Jason J.; Villarrubia González, Gabriel; Fernández-Caballero, Antonio; Navarro, Elena; González, Pascual; Carneiro, Davide; Pinto, António; Campbell, Andrew T.; Durães, Dalila; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The aim of the book is to introduce new developments in Ambient Intelligence from researchers of several countries. The book includes different works in the area of Ubiquitous Computing, e-Health, Ambient Assisted Living, Distributed Computing and Context Aware Computing that have been selected by an international committee. The studies have been presented in the 9th International Symposium on Ambient Intelligence held in Toledo in June 2018.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence